2004
DOI: 10.1111/j.1600-0420.2004.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐ophthalmological findings in sarcoidosis

Abstract: ABSTRACT.Purpose: This review emphasizes the importance of neuro-ophthalmological signs and symptoms in sarcoidosis. The presence of ophthalmological and neuro-ophthalmological findings may lead to diagnosis of the disease and the initiation of adequate treatment. Material and Methods: Patients who had been diagnosed with neurosarcoidosis during the period 1990 À 2001 were identified from the departmental diagnostic index. The history, clinical, laboratory and imaging data of patients were analysed. Results: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
2
29
1
Order By: Relevance
“…6,17,22,33,47,61,62 In the absence of thyroid orbitopathy, orbital biopsy and histopathology may be required before onset of therapeutic intervention. Although corticosteroids are typically used in initial therapy, some idiopathic chronic forms of OID may be poorly responsive and require other therapeutic modalities including radiation therapy or immune modulation.…”
Section: Orbital Involvement In Oidmentioning
confidence: 99%
“…6,17,22,33,47,61,62 In the absence of thyroid orbitopathy, orbital biopsy and histopathology may be required before onset of therapeutic intervention. Although corticosteroids are typically used in initial therapy, some idiopathic chronic forms of OID may be poorly responsive and require other therapeutic modalities including radiation therapy or immune modulation.…”
Section: Orbital Involvement In Oidmentioning
confidence: 99%
“…The pathophysiological mechanism of the facial palsy is implicated in granulomatous mass, chronic meningitic reaction or secondary infl ammation in the parotid gland. Previous MRI studies suggested variable changes in patients with neurosarcoidosis [1][2][3]. With respect to cranial nerve palsy, Oki et al fi rst described a case that MRI showed enhanced mass in the distal internal auditory canal portion of the VII cranial nerve [5].…”
Section: Discussionmentioning
confidence: 99%
“…Of the cranial nerve involvement, the optic nerve was the most frequent lesion (35-38%) and the facial nerve was the second most common (11-19%) [1,2]. Otherwise, 4 or more kinds of cranial neuropathies were extremely rare in neurosarcoidosis [3,4]. The optic nerve is damaged by optic neuritis, intracranial hypertension or mass effect of intraorbital granuloma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations